An update on inflammatory choroidal neovascularization: epidemiology, multimodal imaging, and management - Aniruddha Agarwal (Journal of Ophthalmic Inflammation and Infection, 2018)
Abstract Inflammatory choroidal neovascular membranes are challenging to diagnose and manage. A number of uveitic entities may be complicated by the development of choroidal neovascularization leading to a decrease in central visual acuity. In conditions such as punctate inner choroidopathy, development of choroidal neovascularization is extremely common and must be suspected in all cases. On the other hand, in patients with conditions such as serpiginous choroiditis, and multifocal choroiditis, it may be difficult to differentiate between inflammatory choroiditis lesions and choroidal neovascularization. Multimodal imaging analysis, including the recently introduced technology of optical coherence tomography angiography, greatly aid in the diagnosis and management of inflammatory choroidal neovascularization. Management of these neovascular membranes consists of anti-vascular growth factor agents, with or without concomitant anti-inflammatory and/or corticosteroid therapy.